Tindak Tutur Ekspresif Pada Novel Lima Sekawan: Menyamarkan Teman Karya Enid Blyton - Yasinta, Syahla Ayu; Rohmadi, Muhammad (STKIP PGRI Ponorogo Press, 2024)
Language is a tool for connecting and communicating between individuals as humans who feel, think and also desire. Politeness in language is a characteristic of good communication. Speech acts can be understood as utterances that are used to express an intention so that it can be understood by the listener. Speech acts are divided into 3 types, namely locutionary acts, illocutionary acts and perlocutionary acts. Expressive speech acts are classified as illocutionary speech acts. This study used descriptive qualitative method. The object studied as a source of data in this research is the novel Lima Sekawan: Menyamarkan Teman by Enid Blyton, which was published in its 21st printing in 2022. Data collection was carried out using documentation techniques, namely by note-taking techniques in the form of a data inventory using a format. In the novel Lima Sekawan: Disguising Friends there are eight expressive speech acts, namely expressive speech acts of praising, expressive speech acts of criticizing, expressive speech acts of hope, expressive speech acts of complaining, expressive speech acts of anger, expressive speech acts of apologizing, expressive speech acts of belittling, acting expressive speech saying thank you.